ANALISIS PENGAWASAN KUALITAS PRODUK PADA PERUSAHAAN PAVING BLOCK KETAPANG JAYA PURWOKERTO - Herni Utami Rahmawati (Pro Bisnis, 2010)
This research is a case study at "Ketapang Jaya" poving block companyPurrrokerto entitled "Produd Sualtty Control Analysis At Ketapang Jaya PavingBlock Company Purwokerto", The aims of research are first to find out the defaultrate of paving block product and then to look for whether there is a diference or notbetween the average of default in finished product of plain six sided paving block andmotives six sided poving block. The proposed hypotheses of research are : (l) Theproduct default happened in plain six sided and motives six sided paving block is stillunder the control limit. (2)There is no significant diffirence between the averageproduct default in plain six sided paving block and motives six sided paving blockAs the result of analysis, it can be concluded that the default rate for plain six sidedpaving block is 5,2496 with the upper control limit (UCL) is 0,1316 and the lowercontrol limit (LCL) is 0 (zero) whereas the default late for motives six sided pavingblock is 6,24% u)ith the upper contol limit (UCL) 0,15I 5 and the lower control limit(LCL) rs 0 (zero). As implication, in order to be able to increase company's productquality, the company has to increase its control on its labors especially indepartments of printing, raw malerial, equipments and the increasing of the role oflabors in realizing the importance of quality standard.